Understanding microeconomics - Heilbroner, Robert L.; Thurow, Lester C. (Englewood Cliffs, N.J. : Prentice-Hall, 1975)
The books described some of the basic rules of microeconomics. It's a key to understanding economics as it affects our lives. It aids the understanding of the problems of poverty, the distribution of income, ecology, giant corporations, and all important workings of the market mechanism.
Includes index.
Includes bibliographical references and index.
asm 23/01/2019
Loans
Keywords: Microeconomics